Website Creation About Typical Indonesian Cuisine - Wardani Febrina; Surya Masniari Hutagalung (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2024)
The purpose of this study is to describe the process of creating a website about Indonesian cuisine and describe the results of creating the website. In this qualitative descriptive study, the investigation process uses the Thiagarajan 4D development model phase. The data in this study are based on information obtained from interviews with 4 Minang/Malay restaurants. The data collection technique used is interviews. The process of creating a website for Indonesian cuisine is a presentation of Malay recipes by adhering to Thiagarajan's 4D theory, there are 4 phases of media development carried out, namely: 1) definition, 2) planning, 3) development, 4) distribution. The result of creating a website for traditional Indonesian cuisine is a website that contains a presentation about the history of this cuisine, recipes, and step-by-step instructions on how to prepare Indonesian cuisine, especially Malay cuisine.